Primary Healthcare Providers' Activities in Linking Patients With Chronic Diseases to Community Organizations: A Scoping Review - Nevena Grgurevic; Maud-Christine Chouinard; Édith Ellefsen; Émilie Hudon; Catherine Hudon (SAGE Publishing, 2024)
Context: Aging and increasing comorbidities in the population are leading to more complex care for patients and primary healthcare providers. Community organizations (COs) may play a role in the services offered to support patients with chronic diseases (PCDs) but there are currently no clear guidelines to support primary healthcare providers in linking patients to COs. Objectives: The aim of this study was to describe the role of primary healthcare providers regarding linking PCDs to COs by: (1) describing linking activities; and (2) identifying the main facilitators and barriers associated with these activities. Methods: This scoping review was based on the Arksey and O'Malley method, completed by Levac, Colquhoun, and O'Brien. Related keywords were used in 7 databases to search relevant studies. After the initial screening, 135 full texts were assessed for eligibility by 2 reviewers using inclusion/exclusion criteria. Empirical studies describing activities performed by primary healthcare providers in linking PCDs to COs or describing facilitators or barriers to linking activities were included. Studies describing activities linking to other services than COs or located in emergency departments were excluded. Results: In total, 28 studies were included. Information reported in the studies was classified into 8 main linking activities: capacity development, patient identification, assessment, information, planning, referral, follow-up, and collaboration. Facilitators and barriers to these activities were related to intrapersonal characteristics of providers and patients, professional practice, work environment, relationships, and external influences. Healthcare providers' involvement was often adapted according to their field of practice. Conclusion: This scoping review details the role of primary healthcare providers when linking PCDs to COs in a collaborative and interdisciplinary context, which can be adapted to clinical practice by providers, experts, or stakeholders to support improvement in chronic care management.